Noise annoyance and cardiovascular disease risk: results from a 10-year follow-up study - Hahad, Omar; Gilan, Donya; Michal, Matthias; Tüscher, Oliver; Chalabi, Julian; Schuster, Alexander K.; Keller, Karsten; Hobohm, Lukas; Schmitt, Volker H.; König, Jochem; Lackner, Karl; Wild, Philipp; et al. (Scientific reports, 2024)
The relationship between noise annoyance and risk of cardiovascular disease (CVD) still needs to be fully elucidated. Thus, we examined the relationship between noise annoyance and CVD risk in a large population-based cohort study. Cross-sectional (N = 15,010, aged 35-74 years, baseline investigation period 2007-2012) and prospective data (5- and 10-year follow-up from 2012 to 2022) from the Gutenberg Health Study were used to examine the relationship between noise annoyance due to different sources and risk of prevalent and incident CVD comprising atrial fibrillation, coronary artery disease, myocardial infarction, stroke, chronic heart failure, peripheral artery disease, and venous thromboembolism. In cross-sectional analyses, noise annoyance was an independent risk factor for prevalent CVD, with the strongest associations seen for noise annoyance during sleep (e.g., neighborhood noise annoyance: odds ratio 1.20, 95% confidence interval 1.13-1.27, p < 0.0001). While in the 10-year follow-up, mostly positive associations (although not significant) between noise annoyance and incident CVD were observed, no indication of increased CVD risk was observed after 5 years of follow-up. Noise annoyance due to different sources was associated with prevalent CVD, whereas only weak associations with incident CVD were found. Further large-scale studies are needed to establish the relationship between noise annoyance and risk of CVD.
Gesehen am 28.06.2024